(2-Bromoacetyl)ferrocene - Wu, Xiang-Xiang; Zhu, Xin; Ma, Qiu-Juan; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title molecule, [Fe(C5H5)(C7H6BrO)], the C atoms of the substituted ring have disparate Fe-C bond lengths compared with the unsubstituted ring. In the bromoacetyl residue, the Br and O atoms are co-planar [the O-C-C-Br torsion angle is 5.7 (4)degrees] and are syn to each other. Helical supramolecular chains along the b axis are formed in the crystal structure mediated by C-H center dot center dot center dot O contacts; the carbonyl-O atom is bifurcated. The chains are linked into layers by C-H center dot center dot center dot pi (unsubstituted ring) interactions that stack along the a-axis direction.